2017
DOI: 10.1002/14651858.cd003211.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Feed thickener for infants up to six months of age with gastro-oesophageal reflux

Abstract: Feed thickener for infants up to six months of age with gastro-oesophageal reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 74 publications
0
41
4
2
Order By: Relevance
“…A Cochrane meta‐analysis concluded that the observed reduction of two episodes of regurgitation per day is likely to be of clinical significance to caregivers . Moreover, cornstarch‐thickened formula showed a significant reduction in regurgitation frequency with −1.98 [−2.35; −1.61] episodes per day, which is less than the results of the present study. For locust bean gum, the decrease of −1.47 [−3.13; 0.19] regurgitation episodes per day is also lower than the present results but with a high heterogeneity between the studies .…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…A Cochrane meta‐analysis concluded that the observed reduction of two episodes of regurgitation per day is likely to be of clinical significance to caregivers . Moreover, cornstarch‐thickened formula showed a significant reduction in regurgitation frequency with −1.98 [−2.35; −1.61] episodes per day, which is less than the results of the present study. For locust bean gum, the decrease of −1.47 [−3.13; 0.19] regurgitation episodes per day is also lower than the present results but with a high heterogeneity between the studies .…”
Section: Discussioncontrasting
confidence: 89%
“…A review concluded that thickened formulae reduce the frequency and severity of regurgitations and are indicated in formula‐fed infants with persisting symptoms despite reassurance and appropriate feeding volume intake . A Cochrane meta‐analysis concluded that the observed reduction of two episodes of regurgitation per day is likely to be of clinical significance to caregivers . Moreover, cornstarch‐thickened formula showed a significant reduction in regurgitation frequency with −1.98 [−2.35; −1.61] episodes per day, which is less than the results of the present study.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Our recent Cochrane review 4 identified eight randomised clinical trials analysing the impact of feed thickener in 637 healthy term formula feeding infants up to 6 months of age with symptoms of GOR or abnormal oesophageal pH probe measurement. The trials compared feed thickened with various thickeners including carob bean gum, rice cereal, corn starch or alginate, with unthickened feed, over a 1–8 weeks period.…”
Section: Evidencementioning
confidence: 99%